PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Nuris, Dita; Beti Istanti Suwandayani; Rochana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the learning outcomes of grade V elementary school students in learning Indonesian through the application of the Problem-Based Learning (PBL) model integrated with the Culturally Responsive Teaching (CRT) approach. This study used students of class V-A SD Muhammadiyah 04 Batu City as participants. This research uses the Classroom Action Research (PTK) approach by Kemmis and McTaggart which consists of four stages, namely planning, implementation, observation, and reflection. The implementation of this research consisted of two cycles with each cycle carried out for two meetings. The results showed a significant increase in student learning outcomes from cycle I to cycle II. This is evidenced by the acquisition of the percentage of learning outcomes in cycle I of 35.48% in the very good category and 10.34% in the good category, while in cycle II it was 51.72% in the very good category and 31.03% in the good category. The increase occurred due to the application of the PBL model integrated with the CRT approach which encourages active participation of students and creates meaningful learning.